2016
DOI: 10.1111/aje.12278
|View full text |Cite
|
Sign up to set email alerts
|

The effect of territory quality on female preference in Metriaclima zebra

Abstract: The cichlid fishes of Lake Malawi are an excellent model group with which to study adaptive radiation and speciation; due to the vast number of individual species, large variation in feeding adaptations and behaviours, and relatively recent divergence are found. Males of many cichlid species will obtain and defend lek‐like territories, where they court potential mates in addition to foraging for food. Aspects of territory quality warrant investigation because of the relationship between reproductive success an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This would suggest that the blue flank coloration of mbuna males may evolve to increase conspicuousness in their habitat which has a blue-shifted ambient light spectrum ( Seehausen et al 2008 ; Dalton et al 2010 ; Smith et al 2012 ). Moreover, in our experimental settings, males did not hold a resource or territory that influence female mate choice in M. zebra ( Greenberg et al 2016 ), so the dominance perceived by nuptial coloration may be insufficient to elicit a sexual or reproductive context such as the female choice between dominant and subordinate males.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This would suggest that the blue flank coloration of mbuna males may evolve to increase conspicuousness in their habitat which has a blue-shifted ambient light spectrum ( Seehausen et al 2008 ; Dalton et al 2010 ; Smith et al 2012 ). Moreover, in our experimental settings, males did not hold a resource or territory that influence female mate choice in M. zebra ( Greenberg et al 2016 ), so the dominance perceived by nuptial coloration may be insufficient to elicit a sexual or reproductive context such as the female choice between dominant and subordinate males.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the nuptial coloration of territorial males reflecting blue and UV wavelength may not only increase the conspicuousness of the males but may also provide females with information for choosing a better mate. Previous studies showed that females have a preference for dominant conspecific males ( Mellor et al 2012 ) and males with more food resources ( Greenberg et al 2016 ). However, it has not yet been tested if the blue flank or UV reflective bands in male nuptial coloration influence the female perception of mbuna males ( Jordan et al 2004a ; Pauers et al 2016 ).…”
mentioning
confidence: 99%